Iterative detection of multicode DS-CDMA signals with strong nonlinear distortion effects - Dinis, Rui (2009)
Whenever a direct-sequence code-division multiple-access (DS-CDMA) signal is the sum of several components associated with different spreading codes [e.g., the DS-CDMA signal to be transmitted by the base station (BS) in the downlink or any multicode DS-CDMA signal], it has high envelope fluctuations and a high peak-to-mean envelope power ratio (PMEPR), setting strong linearity requirements for the power amplifiers. For this reason, it is desirable to reduce the envelope fluctuations of the transmitted signals. The use of clipping techniques combined with frequency-domain filtering was shown to be an effective way of reducing the envelope fluctuations (and, inherently, the PMEPR) of DS-CDMA signals, while maintaining the spectral occupation of the corresponding conventional DS-CDMA signals. To avoid PMEPR regrowth effects, the clipping and filtering operations can be repeated several times. However, the performance degradation due to nonlinear distortion effects on the transmitted signals can be relatively high, particularly when a very low PMEPR is intended (e.g., when a low clipping level and several iterations are adopted). This can particularly be serious if different powers are assigned to different spreading codes. To avoid significant performance degradation in these situations, we consider an improved receiver where there is an iterative estimation and cancellation of nonlinear distortion effects. Our performance results show that the proposed receiver allows significant performance improvements after just a few iterations, even when we have strong nonlinear distortion effects.